Factors associated with depressive symptoms in patients with benign prostatic enlargement - Husni H. Abdalla; Jasmit Shah; Tabitha A.N. Nyanja; Jacob S. Shabani (AOSIS, 2023)
Background: Depression is a common condition that may lead to suicide at its worst. It is considered one of the primary causes of morbidity globally. Among the urological causes of depression is benign prostatic enlargement (BPE). Aim: To determine the prevalence and factors associated with depressive symptoms among BPE patients. Setting: This study was conducted in the Urology and Family Medicine Clinic at the Aga Khan University Hospital, Nairobi and Urology clinic at the Aga Khan Hospital Mombasa. Methods: The study was a cross-sectional design recruiting 308 males above the age of 40. Patient Health Questionnaire-9 and International Prostate Symptom Score (IPSS) were used to assess depressive symptoms and lower urinary tract symptoms (LUTS), respectively. Association between depressive symptoms and LUTS was determined. Factors associated with depressive symptoms were analysed by logistic regression. Results: Prevalence of depressive symptoms among patients with symptomatic benign prostatic enlargement (sBPE) was 42.90%. Factors associated with depressive symptoms included comorbid conditions, medication side effects, reduced libido, alcohol use, disturbed sleep at night and anxiety in regard to the prostate condition. Conclusion: There is a high prevalence of depressive symptoms among men with BPE. Assessment and early intervention for depressive symptoms among men with BPE should be initiated before clinical depression sets in. Contribution: The study has created a knowledge base on factors associated with depressive symptoms among men with sBPE in the African context.